Asuhan Kebidanan Pada Ibu Hamil Dengan Emesis Gravidarum Di PMB Asnidar Wilayah Kerja Puskesmas XIII Koto Kampar 2 Tahun 2024 - Nurnila, Nurnila; Nislawaty, Nislawaty (Evidence Midwifery Journal, 2024)
Emesis gravidarum is a common complaint that accompanies pregnancy but causes discomfort, if excessive it can become hyperemesis which will have a bad impact on the mother and fetus. The aim of the research is to provide midwifery care to pregnant women with Emesis gravidarum at PMB Asnidar Working Area of ??Puskesmas XIII Koto Kampar on 14 June – 18 June 2024. The results of this case study research given to Mrs. J with 3 visits in 5 days were that the mother said that nausea and vomiting had reduced. The midwifery care provided is in the form of providing counseling about emesis gravidarum. Treatment consists of providing papermint aroma therapy. Based on the pregnancy care provided to Mrs. J aged 25 years G2P1A0H1, it was found that nausea and vomiting had reduced. The conclusion was that the care provided was carried out well and produced positive results. It is hoped that the results of this case study can add references that can be used for subsequent research